Stress and anxiety among adolescents, during the covid-19 outbreak - Ifdil Ifdil; Yola Eka Putri; Berru Amalianita (Konselor, 2021)
Covid-19 affects every aspect of human life, especially psychological aspects. Furthermore, adolescents experience difficulties because of the pandemic and therefore require extra change due to the occurring situation. In this situation, adolescents felt stress from having to adjust to the unpredictable situation, as well as anxiety, from facing an uncertain situation. Meanwhile, from the previous year, the news has been updated daily, concerning the number of deaths and positive cases. Teens are able to access news through the internet by listening, watching or imagining the current situation. This study used Indonesian adolescent as the research subjects and was conducted online through survey Monkey platform. A total of 98 participants aged above 17 years were obtained from several provinces and region in Indonesia. In addition, the study used DASS as the instrument of research DASS, while the data was analyzed using JASP. According to the results, the stress and anxiety of adolescents during the covid-19 outbreak are in the heavy and very heavy categories, respectively, indicating tremendous pressure is experienced due to the Covid-19 pandemic.